PowerPoint presentation on Revisiting Retro-Technology to Extend Educational Opportunity to Teachers in Remote Schools - Teo, Jimmy Hui Thian; Widad Othman; Shawira Abu Bakar (2010)
A PowerPoint presentation on 'Revisiting Retro-Technology to Extend Educational Opportunity to Teachers in Remote Schools' presented during OUM Seminar Series 05/2010 on 14 May 2010 at OUM Theatrette.